2009
DOI: 10.1007/s00198-008-0824-7
|View full text |Cite
|
Sign up to set email alerts
|

External hip protectors are effective for the elderly with higher-than-average risk factors for hip fractures

Abstract: Risk of hip fracture can be reduced by hip protectors among elderly women with fall history and low BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
21

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 30 publications
1
26
0
21
Order By: Relevance
“…While there is controversy about the efficacy of hip protectors from clinical studies (Koike et al, 2009;Kiel et al, 2007;Parker et al, 2006;Forsen et al, 2004;Birks et al, 2004;O'Halloran et al, 2004;van Schoor et al, 2003;Meyer et al, 2003;Harada et al, 2001;Kannus et al, 2000;Chan et al, 2000;Lauritzen et al,1993), this is thought to be due largely to poor adherence in wearing the device, and there is general agreement that they reduce fracture risk if worn at the time of a fall (Cameron et al, 2001(Cameron et al, , 2010(Cameron et al, , 2003Robinovitch et al, 2009;Ekman et al, 1997). However, additional evidence is required to understand the factors that influence both adherence and biomechanical performance.…”
Section: Introductionmentioning
confidence: 93%
“…While there is controversy about the efficacy of hip protectors from clinical studies (Koike et al, 2009;Kiel et al, 2007;Parker et al, 2006;Forsen et al, 2004;Birks et al, 2004;O'Halloran et al, 2004;van Schoor et al, 2003;Meyer et al, 2003;Harada et al, 2001;Kannus et al, 2000;Chan et al, 2000;Lauritzen et al,1993), this is thought to be due largely to poor adherence in wearing the device, and there is general agreement that they reduce fracture risk if worn at the time of a fall (Cameron et al, 2001(Cameron et al, , 2010(Cameron et al, , 2003Robinovitch et al, 2009;Ekman et al, 1997). However, additional evidence is required to understand the factors that influence both adherence and biomechanical performance.…”
Section: Introductionmentioning
confidence: 93%
“…1 Since then, 14 randomized trials of hip protectors in residential aged care facilities have been published with varying results on their efficacy. [2][3][4] The current Cochrane Collaboration systematic review of hip protectors included 11 of these 14 randomized trials carried out in nursing homes and concluded ''accumulating evidence casts some doubt on the effectiveness of the provision of hip protectors in reducing the incidence of hip fractures in older people.'' 5 However, for frail older people in institutional care, pooled data do indicate a significant positive effect of hip protectors.…”
mentioning
confidence: 99%
“…Within 6 respective searches (by category of intervention), there was a total of 22,349 abstracts or citations and 949 full-text papers reviewed in duplicate. Data from 20 randomized controlled trials were included in the final scoping review, including: 7 trials on oral vitamin D (with or without calcium) (total of 12,875 participants) [[25];[27][32], with supplemental information on reference 25 from reference 26], 2 trials on sun exposure (as a form of vitamin D treatment) (total of 522 participants) [33]; [34], 1 trial on alendronate (n = 327 participants) [35], 1 trial on fluoride (including a total of 460 participants) [36], 4 trials on exercise/behavioral, or multimodal interventions (total of 8,165 participants) [37][40], and 5 trials on hip protectors (total of 2,594 participants) [41][45], of which four [41][44] were previously summarized in a prior systematic review by our group [22]) (Table 2). A recent hip protector trial by Kiel et al (2007) [46] was excluded from our review since participants who dropped out or died were substituted with nonrandomized individuals, violating an a priori exclusion criterion for this review [22]; [23].…”
Section: Resultsmentioning
confidence: 99%
“…Fewer than half of studies in this review reported losses to follow-up of less than 10% (excluding deaths) and fewer than half reported the presence or absence of adverse events (Table 3). Most cluster randomized studies reported the unit of randomization [29;37][39;41;44;45] and adjusted the treatment effect analysis for cluster randomization [29;37][39;44]; whereas the ICC was formally reported only in the multimodal intervention trial by Cox et al [38].…”
Section: Resultsmentioning
confidence: 99%